Nanostructured potassium and sodium ion incorporated Prussian blue frameworks as cathode materials for sodium-ion batteries. Issue 40 (8th May 2017) - Liu, Yang; He, Dandan; Han, Ruimin; Wei, Gangya; Qiao, Yun
Abstract : Nanostructured K x Na y MnFe(CN)6 ( x + y ≤ 2) has been synthesized via a facile co-precipitation method. Abstract : Nanostructured K x Na y MnFe(CN)6 ( x + y ≤ 2) has been synthesized via a facile co-precipitation method. As a cathode, KNMF-3 presents a highly reversible capacity of 133.3 mA h g −1 at 20 mA g −1 as well as an excellent rate capacity of 92.0 mA h g −1 at 600 mA g −1 . This material could be a good candidate as a cathode for sodium-ion batteries.